Ethics in Finance and Public Policy: The Ibercorp Case - Valenzuela, José Luis Durá (Journal of business ethics, 1999)
Our research has found that companies which have diverged from traditional management in order to adopt strategies which include ethics, cooperation and a joint vision of management obtain a greater added value. The new challenges of competitiveness require a position of active cooperation between firms and their suppliers, which should be considered as collaborators rather than adversaries. An active cooperation management may well allow the company to improve the quality of its products and its image, speed up delivery to its clients and make its production and trading more agile, thus enhancing the perception the client has of the product. An improved ethical quality in our dealings, generating trust, improving communication and establishing long-term relationships with joint added value, results in higher competitiveness and greater creation of wealth.